Global Environmental Pollution and its Effect on Life Expectancy (Global Journal of Science Frontier Research, 2022)
Current status of global life expectancy increase is explained. Environmental pollution is a threat to human civilization, a threat to life expectancy. The loss of life years and life expectancy in the global context are identified and quantified. The potential gains in life expectancy are also identified and quantified.
Keywords: life expectancy; pollution; effect of pollution